A generalized approach to deduce the impedance and admittance of underground cable containing N semiconductor screens - Swarnankur Ghosh; Supriyo Das (Engineering Science and Technology, an International Journal, 2022)
Cable routines of most of the commercial transient simulation software like EMTP do not have provision for including the contribution of semiconductor screen in cable impedance and admittance model, although mathematical formulations of impedance and admittance of cable with single and double semiconductor screens are available in the existing literature. Here an attempt is made to develop a general impedance and admittance expressions of underground (UG) cable containing N number of semiconductor screens based on electromagnetic analysis of double layer conductor. The same expressions are reproduced based on circuit analysis to verify the exactness of the expressions derived using the electromagnetic approach. Such general formulations bring the possibility of developing a cable routine that can calculate the impedance and admittance of UG cable with any number of semiconductor screens and thus will overcome the limitations of existing cable routines. Next, the proposed general formulations are applied to obtain the impedance and admittance of UG cable with double and single semiconductor screens directly, which becomes identical to the same derived in the existing literature by rigorous mathematical analysis. Finally, the variations of line parameter and wave characteristics of cable containing single and double semiconductor screens as derived from the general formulations, are observed as a function of semiconductor properties. Those variations are found to be identical with the existing results and thus prove the validity of the proposed general formulations.